Accumulation pattern of orally-administered oxytetracycline in juvenile milkfish Chanos chanos (Forskal, 1775) - Labating, Aubrey B. (Miagao, Iloilo College of Fisheries, University of the Philippines, 2014)
Oxytetracycline (OTC) is one of the few approved antibiotics by the U.S. Food and Drug Administration as prophylactic and chemotherapeutic agent in food fish and is widely used in aquaculture. Milkfish juvenile were fed with Oxytetracycline supplemented diets at a dose of 75 mg otc/kg fish/day for 10 days. The OTC concentration in the muscle and serum during the 10th-day feeding was determined using High Performance Liquid Chromatography (HPLC) with UV-Vis detection. Results show that the peak of OTC bioaccumulation in blood serum occurred at day 2 of feeding while the maximum level of bioaccumulation occurred at day 1 of feeding in milkfish tissue. The concentrations of OTC in blood and in tissues significantly dropped down to almost undetectable levels 2 days after the cessation of OTC supplemented diet feeding.
Thesis (M.S. Fisheries-Aquaculture) -- Miagao, Iloilo : U. P. Visayas, April 2014.
Keywords: Aquaculture -- College of Fisheries, UPVisayas